The NeoAPACHE Study Protocol I: Assessment of the Radiographic Pulmonary Area and Long-Term Respiratory Function in Newborns With Congenital Diaphragmatic Hernia - Amodeo, Ilaria; Raffaeli, Genny; Pesenti, Nicola; Macchini, Francesco; Condò, Valentina; Borzani, Irene; Persico, Nicola; Fabietti, Isabella; Ophorst, Marijke; Ghirardello, Stefano; Gangi, Silvana; Colnaghi, Mariarosa; et al. (Frontiers in Pediatrics, 2020)
In newborns with congenital diaphragmatic hernia (CDH), the radiographic lung area is correlated with functional residual capacity (FRC) and represents an alternative method to estimate lung hypoplasia. In a cohort of newborn CDH survivors, we retrospectively evaluated the relationship between radiographic lung area measured on the first day of life and long-term respiratory function. As a secondary analysis, we compared radiographic lung areas and respiratory function between patients undergoing fetal endoscopic tracheal occlusion (FETO) and patients managed expectantly (non-FETO). Total, ipsilateral, and contralateral radiographic areas were obtained by tracing lung perimeter as delineated by the diaphragm and rib cage, excluding mediastinal structures and herniated organs. Tidal volume (VT), respiratory rate (RR), and their Z-Scores when compared to the norm were collected from pulmonary function tests (PFTs) performed at 12 ± 6 months of age. Linear regression analyses using the absolute Z-Score values for each parameter were performed. In CDH survivors, an increase in total and ipsilateral lung area measured at birth was related to a reduction in the absolute Z-Score for VT in PFTs (p = 0.046 and p = 0.023, respectively), indicating a trend towards an improvement in pulmonary volumes and VT normalization. Radiographic lung areas were not significantly different between FETO and non-FETO patients, suggesting a volumetric lung increase due to prenatal intervention. However, the mean Z-Score value for RR was significantly higher in the FETO group (p < 0.001), probably due to impaired diaphragmatic motility in the most severe cases. Further analyses are necessary to better characterize the role of the radiographic pulmonary area in the prognostic evaluation of respiratory function in patients with CDH. Clinical Trial Registration: This trial was registered at ClinicalTrials.gov with the identifier NCT04396028.